Bulk Doping of Millimeter‐Thick Conjugated Polymer Foams for Plastic Thermoelectrics. (24th October 2017) - Kroon, Renee; Ryan, Jason D.; Kiefer, David; Yu, Liyang; Hynynen, Jonna; Olsson, Eva; Müller, Christian
Abstract: Foaming of plastics allows for extensive tuning of mechanical and physicochemical properties. Utilizing the foam architecture for plastic semiconductors can be used to improve ingression of external molecular species that govern the operation of organic electronic devices. In case of plastic thermoelectrics, utilizing solid semiconductors with realistic (millimeter (mm)‐thick) dimensions does not permit sequential doping—while sequential doping offers the higher thermoelectric performance compared to other methods—because this doping methodology is diffusion limited. In this work, a fabrication process for poly(3‐hexylthiophene) (P3HT) foams is presented, based on a combination of salt leaching and thermally induced phase separation. The obtained micro‐ and nanoporous architecture permits rapid and uniform doping of mm‐thick foams with 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane, while thick solid P3HT structures suffer from protracted doping times and a dopant‐depleted central region. Importantly, the thermoelectric performance of a P3HT foam is largely retained when normalized with regard to the quantity of used material. Abstract : P3HT foams are fabricated through a combination of thermally induced phase separation and salt leaching. The foam architecture shows vastly improved dopant uptake compared to solid P3HT, enabling the superior sequential doping sequence for millimeter‐thick semiconductor structures. The thermoelectric performance of P3HT foams is largely retained per material quantity, implying that foams are attractive for plastic thermoelectrics.